A first glimpse at the Galactic plane with the ASKAP: the SCORPIO field. Issue 2 (12th May 2021) - Umana, G; Trigilio, C; Ingallinera, A; Riggi, S; Cavallaro, F; Marvil, J; Norris, R P; Hopkins, A M; Buemi, C S; Bufano, F; Leto, P; Loru, S; et al.
ABSTRACT: In the broad context of the Australian Square Kilometer Array Pathfinder (ASKAP) early-science phase and preparation for the related surveys, we report the first radio observations towards the Galactic plane. The targeted field was chosen to encompass the entire SCORPIO survey, one of the several pathfinder projects for the Evolutionary Map of the Universe survey planned with the ASKAP. The observations were carried out in 2018 January at a central frequency of 912 MHz, with 15 operational antennas, and covered a total area of about 40 square degrees in three different pointings. The final image has a resolution of 24.1 × 21.1 arcsec 2 and a median rms of 541 μ Jy beam^-1 . We were able to extract 3545 candidate sources, 75 per cent of them point sources. For a preliminary validation, a comparison with the 843 MHz Molonglo Galactic Plane Survey is presented. Although the present observations were obtained with the ASKAP only partially deployed, its unique capability to map complex sources, such as those inhabiting the Galactic plane, at different angular scales, is highlighted. Within the SCORPIO field all the previously classified H ii regions, Planetary Nebulae (PNe), and supernovae remnants (SNRs), previously known to be radio sources, were detected. We also report new radio detections from several H ii regions previously classified as 'candidates' or 'radio quiet' and from half of all the PNe in the SCORPIO field with robust classification. Most notably, we find numerous unclassified, extended sources which constitute a promising sample of candidates H ii regions and SNRs.